Discovery of dihydroisoquinolinone derivatives as novel inhibitors of the p53–MDM2 interaction with a distinct binding mode. Issue 17 (1st September 2015) - Gessier, François; Kallen, Joerg; Jacoby, Edgar; Chène, Patrick; Stachyra-Valat, Thérèse; Ruetz, Stephan; Jeay, Sébastien; Holzer, Philipp; Masuya, Keiichi; Furet, Pascal
Graphical abstract